2015
DOI: 10.1248/bpb.b14-00315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psilocin on Extracellular Dopamine and Serotonin Levels in the Mesoaccumbens and Mesocortical Pathway in Awake Rats

Abstract: Psilocin (3-[2-(dimethylamino)ethyl]-1H-indol-4-ol) is a hallucinogenic component of the Mexican mushroom Psilocybe mexicana and a skeletal serotonin (5-HT) analogue. Psilocin is the active metabolite of psilocybin (3-[2-(dimethylamino)ethyl]-1H-indol-4-yl dihydrogen phosphate).In the present study, we examined the effects of systemically administered psilocin on extracellular dopamine and 5-HT concentrations in the ventral tegmental area (VTA), nucleus accumbens, and medial prefrontal cortex of the dopaminerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 33 publications
(43 reference statements)
6
34
0
2
Order By: Relevance
“…Kuypers et al ( 2016 ) investigated participants after the intake of large doses of Ayahuasca, which is hardly comparable to the microdoses used in the present study. Previous research has shown a relationship between 5-HT 2A receptor activity and goal-directed behavior likely due to indirect modulation of DA release (Vollenweider et al 1999 ; Sakashita et al 2015 ; Dalley et al 2002 ; Boureau and Dayan 2011 ). Dopamine-related adaptive behavior follows an inverted U shape (van Velzen et al 2014 ), suggesting that smaller doses, such as the microdoses ingested by the participants in our current study, are more likely to move participants towards the most efficient mid-zone of the performance function than higher doses do (see Akbari Chermahini and Hommel 2012 , for an application of this rationale on the impact of dopaminergic manipulations on creativity).…”
Section: Discussionmentioning
confidence: 98%
“…Kuypers et al ( 2016 ) investigated participants after the intake of large doses of Ayahuasca, which is hardly comparable to the microdoses used in the present study. Previous research has shown a relationship between 5-HT 2A receptor activity and goal-directed behavior likely due to indirect modulation of DA release (Vollenweider et al 1999 ; Sakashita et al 2015 ; Dalley et al 2002 ; Boureau and Dayan 2011 ). Dopamine-related adaptive behavior follows an inverted U shape (van Velzen et al 2014 ), suggesting that smaller doses, such as the microdoses ingested by the participants in our current study, are more likely to move participants towards the most efficient mid-zone of the performance function than higher doses do (see Akbari Chermahini and Hommel 2012 , for an application of this rationale on the impact of dopaminergic manipulations on creativity).…”
Section: Discussionmentioning
confidence: 98%
“…We chose to include a high (10 mg/kg) dose, which is higher than those commonly reported in the published literature [for review see (Halberstadt and Geyer, 2018)], because of the lower 5-HT 2A affinity in rats compared with humans (Gallaher et al, 1993). Furthermore, microdialysis studies showed that dopamine levels in the nucleus accumbens (NAc) are strongly altered, selectively, by 10 mg/kg psilocin and not by 1 or 5 mg/kg (Sakashita et al, 2015). This could be relevant to its antidepressant effect, as the human doses that produce a therapeutic effect (0.30-0.35 mg/kg) have also been found to increase dopamine levels in ventral striatum (NAc and olfactory tuberculum) in human PET studies (Vollenweider et al, 1999).…”
mentioning
confidence: 99%
“…In line with this, psilocin has been shown to induce dopamine release in the striatum in humans (Vollenweider et al, 1999) and, more recently, also in the nucleus accumbens of male Wistar rats, although only with a very high dose of 10 mg/kg of psilocin (Sakashita et al, 2015). One plausible explanation is that a 5-HT1A antagonist could unmask less significant agonism on 5-HT 1B/D receptors (Tyls et al, 2014).…”
Section: Females MD Females Pe Malesmentioning
confidence: 81%